Cellular Transporters for Ochratoxin A - Saichol, Piraya; Porasuphatana, Supatra (Thai Journal of Toxicology, 2018)
Ochratoxin A (OTA) is a mycotoxin produced by several fungi species and found contaminated in foods. OTA exerts various toxicities including nephrotoxicity, hepatotoxicity, neurotoxicity, teratogenicity and immunotoxicity. The main target organ of OTA has been reported to be kidney. Study of molecular transport of OTA can be essential to develop profound understanding in OTA kinetics throughout the body. Membrane transporters found to be involved in OTA transport include organic anion transporters (OATs), organic transporter polypeptide (OATPs), breast cancer resistant protein (BCRP) and multidrug resistant proteins (MRPs). OAT1, OAT3 and OAT4 play a major role in cellular absorption of OTA in renal tubules. The same statement could be applied to a novel human organic anion transporter NPT4 and OATP1A2 that present at proximal tubular cells. OATP2B1 localized at intestinal cells might facilitate uptake of dietary OTA from the intestinal lumen. Meanwhile the expression of OATP1B1 and OATP2B1 at liver sinusoidal membrane could increase metabolism and excretion of OTA out of the cells. The net effect of OATP-mediated OTA transport in the body is dependent on its localization on each tissue. BCRP, MRP2 and MRP4 are efflux transporters and can reduce the net uptake of OTA into the cells and thus reduce OTA toxicity. The cellular transport of OTA is found to be pH dependent with increasing transport when pH decreases, which might be due to the changing in ionic portion of OTA. Overall, the knowledge on molecular transportation of OTA in various tissues could be applied for further development of strategic prevention of OTA- induced toxicity.